Rural America and Coronavirus Epidemic: Challenges and Solutions - Ameh, Governor G.; Njoku, Anuli; Inungu, Jeff; Younis, Mustafa (European Journal of Environment and Public Health, 2020)
There are emerging concerns about the preparedness of rural communities in the United States in the face of the 2019 novel coronavirus (called SARS-CoV-2, causing the disease COVID-19) considering the existing disparities across the social determinants of health between rural and urban Americans. Taking into account the current exponential rate of spread of the coronavirus, this article critically examines the risk facing the 60 million Americans living in rural areas, discusses possible solutions pertaining to rural COVID-19 prevention, and examines measures to consider to prepare for this epidemic before it reaches rural areas.
Keywords: dept.pch; peer-reviewed

Anxiety and Depression among Breast Cancer Patients Undergoing Treatment in Ghana - Kyei, K. A.; Oswald, J. W.; Njoku, A. U.; Kyei, J. B.; Vanderpuye, V.; Tschida, P. (African Journal of Biomedical Research, 2020)
Breast cancer patients undergoing radiotherapy often experience severe levels of anxiety and depression within the African context. There is a gap in the research literature from Africa, particularly Ghana, with few studies focusing on depression among patients undergoing radiation treatment. The purpose of the study was to find various interventions for depression and anxiety among breast cancer patients in Ghana. A mixed method study examined breast cancer patients undergoing radiotherapy and their responses through a concurrent triangulation involving an interview with selected professional and a detailed patient survey. In all, 100 patients between the ages of 20-89 completed a questionnaire and individual interviews were held with 6 professionals with a minimum of 5 years of work experience. Themes were generated through open coding of the interview data, while multiple regression was performed to determine the relationship between depression and anxiety with the independent variables. In all, 89% had no family history of breast cancer, and the majority (55%) had the disease duration of one to three years. Almost 95% of patients with breast cancer had anxiety and depression in different categories. This included hair loss, discolored finger nails, cost of treatment, and fear of the unknown. Age and monthly income of patients were statistically significant in predicting the anxiety and depression among the patients. Coping mechanisms are essential for all patients undergoing treatment. This study’s implications will lead to positive change when all stakeholders assist in implementing measures to promote coping strategies for breast cancer patients in Ghana.
Keywords: Anxiety; coping; depression; dept.pch; experience; intervention; peer-reviewed

Police brutality against Blacks in the United States and ensuing protests: Implications for social distancing and Black health during COVID-19 - Njoku, Anuli; Ahmed, Yussuf; Bolaji, Bolanle (Journal of Human Behavior in the Social Environment, 2020)
The pandemic of respiratory disease spreading from person-to-person, named “coronavirus disease 2019” (abbreviated “COVID-19”), presents a public health emergency of international concern. This pandemic is occurring during renewed attention to the persistent issue of police brutality against Blacks in the United States. Protests have ensued to highlight perceived and observed injustice against minorities, particularly Black people. Concerns arise that these protests may complicate efforts to adhere to social distancing and increase risks of COVID-19 exposure among Black persons, who are already disproportionality affected by COVID-19 outcomes due to systemic barriers within the healthcare system and society. This article discusses police brutality against Blacks in the United States and subsequent protests, considerations for social distancing and racial disparities in health during COVID-19, and the need for policies to ensure fair and equitable enforcement of social distancing mandates. We also discuss the need for policies to improve access to COVID-19 testing, diagnosis, and management among underserved and minority communities. © 2020 Taylor & Francis Group, LLC.
Keywords: African Americans; COVID-19; Coronavirus; dept.pch; peer-reviewed; police brutality; public health

Looking back and moving forward: SOPHE's 70 years of contributions to health education. - Alber, Julia M.; Allegrante, John P.; Auld, M. Elaine; Breny, Jean M. (Health education & behavior : the official publication of the Society for Public Health Education, 2020)
Founded in 1950, the Society for Public Health Education (SOPHE) provides leadership to the health education profession and promotes the health of all people through six strategic commitments: developing and promoting standards for professional preparation and credentialing of community and school health educators; stimulating research on the theory, practice, and teaching of health education; supporting elimination of health disparities and the achievement of health equity; providing continuing education of the health education workforce; advocating for policy and legislation affecting public health and health promotion; and supporting a network of local chapters. This article describes how SOPHE has pursued these strategic commitments during the past 70 years and discusses challenges that will influence the future of SOPHE and the contours of the research and practice agendas of the field going forward. © 2020 Society for Public Health Education.
Keywords: Education, Public Health Professional; Health Education; Health Educators; Health Promotion; Humans; Public Health; SOPHE; accreditation; achievement; article; credentialing; dept.pch; education; health disparity; health education; health educator; health equity; health promotion; history; human; human experiment; law; leadership; medical education; occupation; peer-reviewed; public health; school health service; teaching; theory-practice relationship; workforce

Naloxone perspectives from people who use opioids: Findings from an ethnographic study in three states. - Boeri, Miriam W.; Lamonica, Aukje K. (Journal of the American Association of Nurse Practitioners, 2020)
BACKGROUND: Naloxone is an opioid antagonist that can reverse an opioid overdose. Increased opioid-related mortality rates led to greater distribution of naloxone without a prescription and administration of naloxone by laypersons. This study fills a gap in knowledge of naloxone experiences among active users of opioids living in suburban communities. PURPOSE: The purpose of this article is to provide nurse practitioners with an in-depth understanding of current naloxone use practices among people who experience overdose events. The specific aims are to compare access to naloxone in diverse suburban towns, to examine administration differences across settings, and to understand perspectives on naloxone experiences from people who are actively using opioids. METHODOLOGICAL ORIENTATION: The data for this analysis were drawn from an ethnographic study in the suburban towns around Atlanta, Georgia; Boston, Massachusetts; and New Haven, Connecticut. Short surveys and in-depth interviews were collected. Inductive methods were used to compare data across settings. SAMPLE: The sample of 106 included 48% female, 62% White, 24% African American/Black, 13% more than one race, and 21% Hispanic/Latinx. The mean age was 41.35 years. CONCLUSIONS: Differences between study settings in access to naloxone, administration frequency, and delivery systems were found. Findings suggest more education and training is needed in overdose prevention and harm reduction intervention. Studies on delivery systems need to address the increase in fentanyl-related overdoses. IMPLICATIONS FOR PRACTICE: Nurse practitioners can help to target distribution of naloxone in local communities, facilitate collaboration with harm reduction services, and provide evidence-based education and training to laypersons. Copyright © 2020 American Association of Nurse Practitioners.
Keywords: Adult; Analgesics, Opioid; Drug Overdose; Female; Harm Reduction; Humans; Male; Naloxone; Narcotic Antagonists; adult; dept.pch; drug overdose; female; harm reduction; human; male; naloxone; narcotic analgesic agent; narcotic antagonist; peer-reviewed

Non-motor symptoms and striatal dopamine transporter binding in early Parkinson's disease - Liu, Rui; Umbach, David M.; Troster, Alexander; Huang, Xuemei; Chen, Honglei (Parkinsonism & Related Disorders, 2020)
Background: Non-motor symptoms (NMS) are common in Parkinson's disease (PD), but their relationships to nigrostriatal degeneration remain largely unexplored. Methods: We evaluated 18 NMS scores covering 5 major domains in relation to concurrent and future dopamine transporter (DAT) imaging in 344 PD patients from the Parkinson's Progression and Markers Initiative (PPMI). We standardized NMS assessments into z-scores for side-by-side comparisons. Patients underwent sequential DaTSCAN imaging at enrollment and at months 12, 24, and 48. Specific binding ratios (SBR) were calculated using the occipital lobe reference region. We evaluated the association of striatal DAT binding at the four time points with each baseline NMS using mixed-effects regression models. Results: Multiple baseline NMS were significantly associated with DAT binding at baseline and at follow-up scans. REM sleep behavior disorder (RBD) symptoms showed the strongest association – mean striatal SBR declined with increasing RBD symptom z-score (average of time-point-specific slopes per unit change in z-score: βAVG = −0.083, SE = 0.017; p < 0.0001). In addition, striatal DAT binding was linearly associated with increasing baseline z-scores: positively for the memory (βAVG=0.055, SE = 0.022; p = 0.01) and visuospatial (βAVG=0.044, SE = 0.020; p = 0.03) cognitive domains, and negatively for total anxiety (βAVG= −0.059, SE = 0.018; p = 0.001). Striatal DAT binding showed curvilinear associations with odor identification, verbal discrimination recognition, and autonomic dysfunction z-scores (p = 0.001, p = 0.0009, and p = 0.0002, respectively). Other NMS were not associated with DAT binding. Conclusions: Multiple NMS, RBD symptoms in particular, are associated with nigrostriatal dopaminergic changes in early PD. © 2020 Elsevier Ltd
Keywords: Aged; Anxiety; Article; Autonomic Nervous System Diseases; Cognitive Dysfunction; Depression; Disruptive, Impulse Control, and Conduct Disorders; Dopamine Plasma Membrane Transport Proteins; Dopamine transporter binding; Female; Humans; Longitudinal Studies; Male; Middle Aged; Neostriatum; Non-motor symptoms; Olfaction Disorders; Parkinson Disease; Parkinson disease; Parkinson's disease; REM Sleep Behavior Disorder; Substantia Nigra; Tomography, Emission-Computed, Single-Photon; adult; aged; anxiety; autonomic dysfunction; autonomic neuropathy; clinical assessment; clinical evaluation; clinical feature; clinical trial; cognitive defect; cohort analysis; complication; controlled study; depression; dept.pch; depth perception; diagnostic imaging; disease association; dopamine transporter; evidence based practice; female; follow up; human; impulse control disorder; longitudinal study; major clinical study; male; metabolism; middle aged; motor performance; multicenter study; neostriatum; neuroimaging; occipital lobe; parasomnia; pathophysiology; peer-reviewed; priority journal; protein binding; scoring system; single photon emission computed tomography; smelling disorder; striate cortex; substantia nigra; verbal memory

Continuing the Journey Toward Health Equity: Becoming Antiracist in Health Promotion Research and Practice. - Breny, Jean (Health Education and Behavior, 2020)
Health education and promotion researchers and practitioners are committed to eliminating health disparities, and the Society for Public Health Education (SOPHE) has continuously supported this effort through its journals, professional development, annual conferences, and advocacy. The COVID-19 pandemic elucidated inequities directly caused by racism and other social determinants of health. In order to achieve health equity, we need to become antiracist in our research, practice, and advocacy work by standing united against racist policies and practices. I invite us all to heed the call to action on these five points: place racism on the agenda, practice cultural humility, claim your privilege and eliminate microaggressions, utilize strategies that promote inclusion and equity, and embrace your inner leader and activist. Just as SOPHE as an organization pivoted its annual conference from on ground to virtual in March 2020, so can we be innovative and brave as professionals to face the hard work and dedication needed to become antiracist., (C)2020Sage Publications
Keywords: Betacoronavirus; Coronavirus Infections; Coronavirus infection; Health Equity; Health Promotion; Humans; Pandemics; Pneumonia, Viral; Racism; Social Determinants of Health; antiracism; article; dept.pch; ethnology; health education; health equity; health promotion; human; human experiment; leadership; organization and management; pandemic; peer-reviewed; public health; racism; social determinants of health; virus pneumonia

Differences in health behaviors related to overweight/obesity by race/ethnicity in a diverse urban commuter college - Rupp, Kristie; Schnoll, Roseanne; Zigmont, Victoria A. (Journal of American College Health, 2020)
Objective: To examine health behaviors associated with overweight/obesity by race/ethnicity at a diverse urban college. Participants: 270 undergraduates (77.0% female; 26.7% non-Hispanic white) and median body mass index (BMI) of 23.1 kg/m2. Methods: A questionnaire about health-related behaviors as part of the “Get Fruved” project was used to measure health behaviors (sugar sweetened beverage (SSB), fruit and vegetable consumption, physical activity, stress, and sleep) by race/ethnicity. Multivariable logistic regression was used to assess the adjusted odds of engaging in positive health-related behaviors. Results: Non-Hispanic black and Hispanic students were 64% and 59% less likely to consume lower amounts of SSB. Hispanic students were 83% and 81% less likely to meet vegetable and fruit recommendations. Non-Hispanic black and other (including biracial) had reduced odds of meeting vegetable recommendations (AOR = 0.18 and 0.28). Conclusions: Disparities in SSB, fruit, and vegetable consumption represent potential intervention targets to improve health behaviors among racial/ethnic minorities. © 2020 Taylor & Francis Group, LLC.
Keywords: College; dept.hms; dept.pch; health behavior; peer-reviewed; race/ethnicity

Book Review: Lisa M.Sullivan and SandroGaleo, eds. 2019. Teaching Public Health. Baltimore, MD: Johns Hopkins University Press. $46.49. pp. 352. ISBN: 9781421429809. - Jung, Betty C. (World Medical & Health Policy, 2020)
Keywords: book review; book.review; dept.pch

Post-Graduation Impact of a Program Planning Service-Learning Project. - Risisky, Deb; Goldson, Tess; DeMezzo, Robert (Pedagog. health promot., 2020)
Research has shown that service-learning can increase student-learning outcomes across various disciplines. Service-learning opportunities have been steadily increasing in college settings, especially in health-related fields. This evaluation of an undergraduate public health course at a mid-size, public university in New England sought to understand the impact of service-learning on material retention, internships, and post-graduation public health careers. A 25-item questionnaire was emailed to students who took the course between the Fall 2010 and Spring 2016 semesters with 75 completed (33.3% completion rate). More than half of the respondents noted that their participation in a service-learning project positively affected their internship experience, their first post-graduation job, and their overall career, while also helping them retain the course material after graduation. Open-ended responses provided insight to the qualitative responses. Respondents noted that in addition to having the understanding and ability to put on programs in their community, they also had more confidence in their abilities. The opportunity to practice public speaking skills as well as work collaboratively in group settings, were both noted as essential skills needed to succeed in the public health workforce. It was concluded the project had a positive impact on student's learning and retention in planning, implementing, and evaluating an actual health promotion program as well as how they were able to use those skills in their careers., (C)2021Sage Publications
Keywords: dept.fye; dept.pch; dept.rslf; health education; peer-reviewed; program planning; service-learning

Uncertainty in transitions of African American caregivers - Unson, Christine; Flynn, Deborah; Chukwurah, Queendalene; Glendon, Maryann; Testut, Tammy (Issues in Mental Health Nursing, 2020)
The purpose of this study was to gain an understanding of the ambiguities and uncertainties experienced by a diverse group of African-American caregivers. The study applied Schlossberg's transition theory (TT) and Mishel’s revised uncertainty theory to narratives of self-identified African-American caregivers who provided care at least 5 h a week. The men (6) and women (8) were mostly unmarried, mostly caring for a parent or grandparent. The caregivers’ average age was 52 (SD = 19; ages ranged from 24 to 82 years); and the care recipients’ average age was 84 (SD = 9). Six care recipients had dementia and the remainder had multiple disease diagnoses. Narratives were obtained by in-depth interviews or focus group discussions. These were audio-recorded, transcribed verbatim professionally and analyzed independently by trained coders. Schlossberg’s TT contextualized whereas Mishel’s RUIT illuminated the characteristics of the transition, its associated uncertainty, and their relationship to the development of caregiver stress. Situational factors such as difficulties with illness symptoms of the care recipient, conflict between previous experience and current expectations and the adjustments to the new caregiving role, burdened younger caregivers more than older caregivers. Self-factors related to lack of knowledge about the illness and feelings of lack of control. Social support was predominantly provided by family members, and its absence resulted in conflict among siblings and caregiver stress. The most common coping strategies include religiosity, expectations of reciprocity, and coming to terms with the uncertainty. Understanding the feelings, perceptions and needs of caregivers in transition is tantamount to providing nursing care.
Keywords: Adaptation, Psychological; Adult; African American; African Americans; Aged; Aged, 80 and over; Caregivers; Female; Grandparents; Humans; Male; Middle Aged; Narration; Parents; Social Support; Stress, Psychological; Uncertainty; Young Adult; adult; aged; caregiver; child parent relation; coping behavior; dept.nur; dept.pch; female; grandparent; human; male; mental stress; middle aged; peer-reviewed; psychology; social support; uncertainty; verbal communication; very elderly; young adult